Victoria Brú Sánchez and the epidemic of influenza in Cienfuegos, 1918 - Reinaldo José Pino Blanco; Rigoberto Flores Roó; Alfredo Dario Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Brief biographical data are exposed about the nurse Victoria Brú Sánchez, such as her birth, childhood and adolescent years. Some factors are mentioned that influenced in their vocational orientation toward the Infirmary, such as her family antecedents and personal experiences when witnessing other epidemics that whipped our population in those years. We refer too her life as student of the School of Nurses in the Hospital Nuestra Señora de las Mercedes de La Habana. It is mentioned as well all the places where she worked after graduation and the different positions that she occupied during its brief, but brilliant, professional life. The most characteristic features in her personality and her self-denying and heroic behavior, are analyzed, principally during the epidemic of Influenza that affected Cienfuegos in the year 1918, moment in which she lost the life trying to help other people.